2020
DOI: 10.3390/nu12071999
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Synbiotic Preparation Containing Lactobacillus and Bifidobacterium Probiotic Strains and Short Chain Fructooligosaccharides in Patients with Diarrhea Predominant Irritable Bowel Syndrome—A Randomized Double-Blind, Placebo-Controlled Study

Abstract: The purpose of the randomized double-blind placebo-controlled trial was to assess the effectiveness of synbiotic preparation containing probiotic Lactobacillus rhamnosus FloraActive™ 19070-2, Lactobacillus acidophilus DSMZ 32418, Bifidobacterium lactis DSMZ 32269, Bifidobacterium longum DSMZ 32946, Bifidobacterium bifidum DSMZ 32403 and fructooligosaccharides in adult patients with diarrhea-dominant IBS (IBS-D). The study included eighty patients with moderate and severe IBS-D who were randomized to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…Lactobacilli spp., E. coli -Nisle 1917, Bifodobacteria spp., some Streptococcus types, and the yeast Saccharomyces boulardii are all considered probiotics [ 60 ]. Recently, their application as adjuvant therapy in IBS treatment mostly showed positive results [ 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. In addition, administration of Akkermansia muciniphila and Lactobacillus sakei OK67 to high-fat diet (HFD) fed mice were independently able to enhance tight-junction function, increasing occludin gene expression and decreasing intestinal permeability [ 125 , 126 ].…”
Section: Main Findingsmentioning
confidence: 99%
“…Lactobacilli spp., E. coli -Nisle 1917, Bifodobacteria spp., some Streptococcus types, and the yeast Saccharomyces boulardii are all considered probiotics [ 60 ]. Recently, their application as adjuvant therapy in IBS treatment mostly showed positive results [ 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. In addition, administration of Akkermansia muciniphila and Lactobacillus sakei OK67 to high-fat diet (HFD) fed mice were independently able to enhance tight-junction function, increasing occludin gene expression and decreasing intestinal permeability [ 125 , 126 ].…”
Section: Main Findingsmentioning
confidence: 99%
“…Synbiotics have demonstrated potential as a promising approach for the treatment of functional bowel disorders, including IBS. A recent randomized, double-blind, placebo-controlled study of adult IBS patients indicated that a synbiotic preparation of probiotic strains of Lactobacillus ( L. rhamnosus FloraActive™19070-2, L. acidophilus DSMZ 32418) and Bifidobacterium ( B. lactis DSMZ 32269, B. longum DSMZ 32946, B. bifidum DSMZ 32403) together with short-chain FOS (scFOS) had beneficial effects in the treatment of IBS-D [ 96 ]. The primary endpoints considered were assessments of symptom severity with IBS-SSS, an improvement of IBS symptoms using the global improvement scale (IBS-GIS), and adequate relief of symptoms after four and eight weeks of therapy.…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
“…rhamnosus FloraActive 19070-2, Lb. acidophilus DSMZ 32418, B. lactis DSMZ 32269, B. longum DSMZ 32946, B. bifidum DSMZ 32403 strains, and scFOS as a prebiotic compound [ 143 ]. Last but not least, in 2020, Seong et al described a synbiotic, containing Lb.…”
Section: Probiotics Prebiotics and Synbiotics In Ibs Treatmentmentioning
confidence: 99%
“…Most of the cited research [54,[134][135][136][137]140,142,143] was conducted as double-blind, placebo-controlled, except from Moser et al (2019) [139], as well as Seong et al (2020) [144], who performed the animal study. Two studies were conducted on people suffering from the IBS-C subtype [136,142], and the other two on subjects with IBS-D [139,143].…”
Section: Synbioticsmentioning
confidence: 99%
See 1 more Smart Citation